Pemetaan Kapasitas Daya Dukung Tanah Untuk Fondasi Dalam Berdasarkan Data Sondir Di Kota Pekanbaru - Irvan Arisma; Agus Ika Putra; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The bearing capacity of the soil can be defined as the ability of the soil to support the load on the foundation of the structure above it. In determining the bearing capacity of the foundation, soil investigation data that is commonly used is based on the Cone Penetrometer Test (CPT) or Sondir Test in the form of end resistance (qc) and frictional resistance (qs). The purpose of thisstudy is to obtain a map that describes the bearing capacity of the soil at a certain depth and type of foundation. 41 CPT test data spread over the area of Pekanbaru city were used to determine the bearing capacity of the soil using the Aoki & De Alencar method and the Meyerhoff method. The type of foundation that is taken in calculating the bearing capacity is a concrete pile foundation with a diameter of 60cm. Based on the calculation results, the averagebearing capacity value for single pile foundations using the Aoki & De Alancer method at a depth of 6 meters, 12 meters, and 18 meters are 45,293 tons, 47,564 tons, and 56,168 tons, respectively. Meanwhile, if using the Meyerhoff method, the average bearing capacity values forsingle pile foundations at the same three depths were obtained respectively 137,952 tons, 233,861 tons, and 300,889 tons. Then the test sites that have adjacent bearing capacity values are connected and plotted in different maps for each method and depth.Keyword: bearing capacity, deep foundation, mapping, sondir test